Specific [3H]glutamate binding in the cerebral cortex and hippocampus of rats during development: effect of homocysteine-induced seizures - Folbergrová, J; Lisý, V; Haugvicová, R; Stastný, F (Neurochemical research, 1997)
Specific [3H]glutamate binding to synaptic membranes from the cerebral cortex and hippocampus of 7-, 12- and 18-day-old rats was examined, both in control animals and during seizures induced by homocysteine. In the cerebral cortex a transient peak of glutamate binding was observed in 7-day-old group, whereas in the hippocampus it occurred in 12-day-old animals. Total specific [3H]glutamate binding was not influenced by preceding seizure activity in either of the age groups and both the studied regions. NMDA- and QA-sensitive glutamate bindings represent the highest portion of the total binding. Moreover, NMDA-sensitive binding in the cerebral cortex of 7-day-old rats is significantly higher as compared to the two more mature groups. The proportion of individual receptor subtypes on total binding in each age group was not influenced by preceding seizure activity. However, NMDA-sensitive binding in the hippocampus of 12-day-old rats, sacrificed during homocysteine-induced seizures, was significantly increased as compared to corresponding controls. In contrast to the effect of NMDA, AMPA, kainate and quisqualate which displaced to a different extent [3H]glutamate binding, homocysteine had no effect when added to membrane preparations. Similarly, [3H]CPP and [3H]AMPA bindings were not affected in the presence of homocysteine. It thus seems unlikely that homocysteine is an effective agonist for conventional ionotropic glutamate receptors. Its potential activity at some of the modulatory sites at the NMDA receptor channel complex or at metabotropic receptors has to be clarified in further experiments.
Keywords: referenční hodnoty; Seizures; Kainic Acid; Quisqualic Acid; tritium; homocystein; Glutamic Acid; analýza rozptylu; záchvaty; stárnutí; Analysis of Variance; Synaptic Membranes; krysa rodu Rattus; Hippocampus; vazebná místa; kyselina alfa-amino-3-hydroxy-5-methyl-4-isoxazolpropionová; zvířata; synaptické membrány; Aging; hipokampus; mozková kůra; Binding Sites; Homocysteine; potkani Wistar; Cerebral Cortex; N-Methylaspartate; alpha-Amino-3-hydroxy-5-methyl-4-isoxazolepropionic Acid; kyselina chischalová; Rats, Wistar; Male; Tritium; N-methylaspartát; Rats; Reference Values; kyselina kainová; Animals; mužské pohlaví; kyselina glutamová